Arthrodesis of the Pubic Symphysis With Compression Plating and Femoral Strut Allograft for Pubic Instability and Osteitis Pubis: A Novel Surgical Technique. Issue 2 (18th June 2022) - Catanzano, Anthony A.; Kollmorgen, Robert; Olson, Steven A.
Abstract : Introduction: Osteitis pubis and pubic instability represent an uncommon, yet a potentially debilitating problem for patients. While many cases are amendable to conservative measures, the few recalcitrant cases present a difficult challenge for surgical management with the risk of implant failure, nonunion, and potential complications. Materials and Methods: A retrospective review of 3 patients undergoing symphyseal arthrodesis with a strut allograft for osteitis pubis and/or pubic instability after failed conservative management was conducted at a single institution. Preoperative evaluation, surgical technique, and postoperative regimen are thoroughly described. Surgical complications, reoperation rate, pain, and Patient-Reported Outcomes Measurement Information System (PROMIS) scores, as well as radiographic outcomes were reported. Results: Three patients undergoing our symphyseal arthrodesis technique after failed conservative management were identified. All patients had an improvement from preoperative pain levels and the 2 patients with >12-month follow-up were able to return to full activity, including 1 patient returning to full active duty in the United States Army. Discussion: The unique technique presented here utilizes both implant fixation, as well as allograft supplementation to improve fusion rates. Although a limited sample with limited follow-up, the early results of this novel technique are encouraging and may represent a more reliable surgical option for patients with chronic, recalcitrant pubic instability.